COMMERCIAL CUTTING OF CARCASS IN BROILER CHICKEN GIVEN DRAGON FRUIT PEEL EXTRACT THROUGH DRINKING WATER - I K. B., Darmawan; Sriyani, N.L.P; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2023)
This study aimed to determine the effect of giving dragon fruit peel juice through drinking water on carcass weight and percentage of commercial broiler chicken carcass (breast, thigh, wing and back), carried out in Buahan Village, Tabanan District, Tabanan Regency, which took place from November 15-December 22 2022. The research design used was a completely randomized design (CRD) with 4 treatments and 4 replications, each using 4 broilers. The treatments were drinking water without dragon fruit peel juice (P0/control), 2% dragon fruit peel juice (P1), 4% dragon fruit peel juice (P2), 6% dragon fruit peel juice (P3). The variables observed included carcass weight and commercial carcass (chest, thighs, wings and back). Based on the results obtained, the carcass weight of P3 showed the highest value of 1034.50 g which was statistically significantly different from P0 (P<0.05) followed by P2 with a value of 1034.00 g and P1 with a value of 998.50 g. The results of the percentage of commercial carcass cut from the chest and thighs showed that the highest value was obtained by P3, and was significantly different from P0 (P<0.05). While on the wings and back, P0 produces the highest value, and P2 produces the lowest value and significantly different (P> 0.05). Giving dragon fruit peel extract in drinking water at a level of 6% (P3) was able to increase the carcass weight and carcass pieces of the breast and thighs of broiler chickens, but was not able to increase the carcass pieces of the wings and back. Key words: broiler chicken, dragon fruit peel, carcass commercial